2013
DOI: 10.1038/jcbfm.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size and Velocity of Injection are Major Determinants of the Safety of Intracarotid Stem Cell Transplantation

Abstract: Intracarotid transplantation has shown potential for efficient stem cell delivery to the brain. However, reported complications, such as compromised cerebral blood flow (CBF), prompted us to perform further safety studies. Glial-restricted precursors (GRPs) and mesenchymal stem cells (MSCs) were transplanted into the internal carotid artery of rats (n ¼ 99), using a microcatheter. Magnetic resonance imaging was used to detect post-transplantation complications, including the development of stroke, for the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 26 publications
5
103
0
Order By: Relevance
“…In consistence with previous findings [18], we found that 3D spheroid culture significantly reduced the size of MSCs *40% (from average diameter 25 mm to average dimmer 15 mm). Cell size has been suggested as a critical parameter of vascular obstructions in a recent study [38]. Our results indicate that 3D-spheroid-cultured MSCs are safer and more effective than conventionally monolayer-cultured MSCs for intra-artery administration.…”
Section: Discussionsupporting
confidence: 59%
“…In consistence with previous findings [18], we found that 3D spheroid culture significantly reduced the size of MSCs *40% (from average diameter 25 mm to average dimmer 15 mm). Cell size has been suggested as a critical parameter of vascular obstructions in a recent study [38]. Our results indicate that 3D-spheroid-cultured MSCs are safer and more effective than conventionally monolayer-cultured MSCs for intra-artery administration.…”
Section: Discussionsupporting
confidence: 59%
“…One recent study that was performed in rats used intracarotid MSC injection for brain cell therapy and reported that cell size, injection speed, and the cell dose are the important factors that determine the occurrence of brain infarction. 17 In this study, 2×10 6 MSC with a diameter of 25 µm resulted in microinfarctions, whereas smaller cells (glialrestricted precursors) with same total cell volume did not cause infarctions. The importance of cell injection speed has also been shown in the pig model of recent myocardial infarction, and a slow rate of injection seems to be better in preventing microinfarctions.…”
Section: Ishikawa Intracoronary Injection Of Large Cellsmentioning
confidence: 99%
“…Intracerebral and intracerebroventricular routes are very invasive alternatives, hardly representing the best clinical options. In this sense, intravascular injections are incomparably more feasible and less troublesome, and allows injections with higher cell doses [142] . However, due to their size, stem cells were reported to get trapped in the lungs, liver and spleen and to cause embolisms, following tail vein and intracarotid injections, respectively [143][144][145] .…”
Section: Preclinical Studies: An Heterogeneous Approach For An Heteromentioning
confidence: 99%